SOCIAL MEDIA AS POLITICAL PARTY CAMPAIGN IN INDONESIA - Abdillah , Leon Andretti (Universitas Bina Darma, 2014)
Social media as a trend in the Internet is now used as a medium for political campaigns. Author explores the advantages and social media implementation of any political party in Indonesia legislative elections 2014. Author visited and analyzed social media used by the contestants, such as: Facebook, and Twitter. Author collected data from social media until the end of April 2014. This article discusses the use of social media by political parties and their features. The results of this study indicate that social media are: 1) effective tool for current and future political campaigns, 2) reach the voters and supporters instantly, 3) used by Political parties to show their logo/icon, and 4) last but not least quick count results also show that political parties which using social media as part of their campaigns won the legislative elections.